DESIGN OF AN ANFIS BASED BLOOD VOLUME CONTROL SYSTEM FOR RATS - Tas, Umit; Akbas, Ahmet (European Scientific Journal, ESJ, 2013)
Adaptive Network-based Fuzzy Inference System (ANFIS) can be employed directly in a wide variety of applications in decision making and control, because ANFIS is a class of adaptive network and it has minimal restrictions on modeling of the system. In this case study, ANFIS based approach has been implemented to develop a control system for the Blood Volume (BV) of rats. In order to achieve this aim, the effects of Glucagonlike Peptide-2 (GLP-2) on BV was used. In order to let the models to represent the forward and inverse relations between the hormonal effects of GLP-2 and BV of rats, the ANFIS models with the cluster partitioning of the data was trained, validated and tested using the clinical data. Therefore, the analysis based on simulations indicates that the control process using ANFIS based controller has sufficient performance .